The Performance Investigation of Bimodal Cation Exchange/Hydrophilic Interaction Liquid Chromatography–Electrospray Ionization Mass Spectrometry by Modifying Mobile Phase Composition in Amino Acid Separation. (25th June 2019) - Lee, Seunghwa; Kim, Hee Won; Han, Sang Moon; Han, Sang Yun; Kim, Byungjoo; Moon, Myeong Hee; Kim, Ki Hun; Lee, Jaeick
Abstract : Owing to its unique selectivity, mixed‐mode chromatography (MMC) has been extended to the analysis of biological fluids. Among various MMC applications, ion exchange/hydrophilic interaction liquid chromatography (IEX/HILIC) is particularly beneficial for the analysis of polar compounds without derivatization or ion pairing. Nevertheless, no practical information about the retention behavior is discussed. In this study, the chromatographic behavior of amino acids in a CEX/hydrophilic interaction mixed‐mode column via the modification of the mobile phase was investigated. A low buffer salt concentration led to increased retention; particularly, positively charged amino acids were not eluted by excessive interactions with the negatively charged stationary phase at a moderate salt concentration (<20 mM). An acid modifier of formic acid or acetic acid exhibited a similar effect on the separation, and a low acid concentration (<0.5%) led to peak broadening by additional ion exchange with a silanol group at high pH. With respect to the composition of organic solvents, aprotic solvents such as tetrahydrofuran or acetonitrile afforded appropriate retention. However, protic solvents led to the considerably reduced retention except positively charged amino acids. Novel, practical information for the optimization or development of applications with a CEX/HILIC column for polar analytes such as amino acids was obtained. Abstract : Chromatographic behavior investigation in amino acid separation by mobile phase adjustment.